Determinants of institutional quality and per capita growth in natural resource-dependent countries - Khalid Adnan Saeed (Cogent Economics & Finance, 2022)
Institutional quality has both short-term and long-term impacts on economic growth. Its short-term impact comes from the quality of institutions ex ante while its long-term impact comes from the quality of institutions ex post. Ex post institutions are shaped by the direct impact of resource dependence on regime type. The goal of this paper is to identify the components of institutional quality that has the most impact on per capita growth in resource-rich developing countries. I investigate the relationship between resource wealth and institutions and their impact on per capita growth by deconstructing institutional quality in a panel of 58 developing countries in the period between 1996 and 2014. I ask if the effect of resource wealth on growth depends on the quality of institutions, then which underlying component(s) of institutional quality have the most effect on this relationship? Results show that voice and accountability have the most influence in shaping institutional quality in a sample of developing countries, and there is evidence that it has the most relevant and significant effect on growth compared to other components of institutional quality.
Keywords: 330; Economic growth; political resource curse; natural resource curse; institutions; MENA